The nursing profession: challenges, intentions to leave and new roles. - gianluca azzellino; Patrizia Vagnarelli (Dissertation Nursing)
In recent years, the nursing profession has been experiencing significant challenges. Despite the efforts made during the COVID-19 pandemic, many nurses today express their intention to leave the profession mainly due to the lack of adequate recognition. In this already difficult context, a new professional figure is emerging, the nursing assistant. However, the introduction of these new support figures may not solve the underlying problems of the nursing profession, on the contrary, it risks further reducing the attractiveness of the profession. Therefore, it is essential to urgently implement policies that improve working conditions and that recognize the value of the nursing profession by offering concrete paths of professional growth.